2017
DOI: 10.1097/md.0000000000006469
|View full text |Cite
|
Sign up to set email alerts
|

Influence of cyclosporine and everolimus on the main mycophenolate mofetil pharmacokinetic parameters

Abstract: The objective of the present study was to assess the effect of cyclosporine (CsA) on the pharmacokinetic parameters of mycophenolic acid (MPA), an active mycophenolate mofetil (MMF) metabolite, and to compare with the effect of everolimus (EVR).Anonymized medical records of 404 kidney recipients were reviewed. The main MPA pharmacokinetic parameters (AUC(0–12) and Cmax) were evaluated.The patients treated with a higher mean dose of CsA displayed higher MPA AUC(0–12) exposure in the low-dose MMF group (1000 mg/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
(50 reference statements)
1
5
0
Order By: Relevance
“…The observed findings imply that SIR may not affect the overall MPA exposure to the extent that CsA does, and it does not impair the primary absorption of MPA . Similar to SIR, renal transplant recipients treated with the combination of EVR and MMF had significantly higher MPA C trough and AUC 0‐12h compared with those treated with CsA . In agreement with clinical findings, in vitro studies found that both SIR and EVR do not affect the hepatic glucuronidation of MPA in human liver microsomes, and it has no inhibitory effect on the MRP2‐mediated MPAG transport .…”
Section: Immunosuppressantssupporting
confidence: 76%
See 1 more Smart Citation
“…The observed findings imply that SIR may not affect the overall MPA exposure to the extent that CsA does, and it does not impair the primary absorption of MPA . Similar to SIR, renal transplant recipients treated with the combination of EVR and MMF had significantly higher MPA C trough and AUC 0‐12h compared with those treated with CsA . In agreement with clinical findings, in vitro studies found that both SIR and EVR do not affect the hepatic glucuronidation of MPA in human liver microsomes, and it has no inhibitory effect on the MRP2‐mediated MPAG transport .…”
Section: Immunosuppressantssupporting
confidence: 76%
“…There is evidence showing that the combination of SIR with MMF following early withdrawal of calcineurin inhibitors is associated with better long‐term clinical outcomes . The combination of EVR and MMF also provides favorable outcomes following transplantation . Therefore, there is a rising trend toward a calcineurin inhibitor–sparing regimen, and the combination of mTOR inhibitors with MMF/EC‐MPS has been increasingly used …”
Section: Immunosuppressantsmentioning
confidence: 99%
“…On the other hand, Pred-CsA-and Pred-CsA-MMFtreated groups demonstrated significantly severe inflammation with pulp tissue disorganization of the pulp and thinner porous layer of mineralized bridge formation than the control group and Pred-treated group. This result may be related to the effect of MMF and CsA immunosuppressive drugs on T lymphocytes and inflammatory cells function leading to improper healing process of the dental pulp [52,53]. A similar finding was reported by Mahmoud et al [24] who concluded that MTA pulp capping technique can be performed on patients treated with corticosteroids like Pred; however, pulp capping should be prohibited in patients under treatment with MMF and CsA immunosuppressive therapy.…”
Section: Discussionmentioning
confidence: 56%
“…Previous studies have already shown that CsA could influence MPA-AUC 0-12h affecting MPA EHC [2] and MPA-Cl [5]. Nevertheless, this PK interaction has been well documented in renal transplant recipients [4,22,23], whereas there is a paucity of data from studies investigating not-renal transplant recipients, where renal clearance and drugs half-life should be less involved.…”
Section: Discussionmentioning
confidence: 98%